Trends of vitamin D in asthma in the pediatric population for two decades: a systematic review - Myongsoon Sung (The Korean Pediatric Society, 2023)
Vitamin D exhibits anti-inflammatory properties through multiple mechanisms. Vitamin D deficiency is associated with increased inflammation, exacerbations, and overall worse outcomes in pediatric asthma and is observed in asthmatic children with obesity. In addition, given the increase in the prevalence of asthma over the last few decades, there has been enormous interest in vitamin D supplementation as a potential therapeutic option. However, recent studies have suggested no strong association between vitamin D levels or supplementation and childhood asthma. Recent studies have reported that obesity and vitamin D deficiency are associated with increased asthma symptoms. Thus, this review summarizes the findings of clinical trials regarding the role of vitamin D in pediatric asthma and analyzes the study trends of vitamin D over the past 2 decades.